The Relationship Between Educational Factors and Early Detection Behavior Cervical Ca in Fertile Age Women - Lilik Darwati; Khusnul Nikmah (Universitas STRADA Indonesia, 2020)
From the results of the study, it is known that almost half of the respondents in the implementation of cervical caesarean education, including less, namely 13 0 respondents and most of the respondents carried out early detection of cervical caverns with Pap smear, as many as 272 respondents out of a total of 369 respondents. There is a relationship between educational factors and the behavior of early detection of cervical caesarean at WUS p value 0.000 <0.05. Education is necessary in order untu k make someone knows d an encouraging someone to carry out early detection of ca cervix. There is a relationship between educational factors on the behavior of early detection of cervical cancer in women of childbearing age because the realization of behavior requires a variety of factors as a predisposition for the realization of behavior